Guittone d’Arezzo and Female Superiority through Paradox: An Antecedent of the Renaissance Querelle des Femmes? - Cerrato, Daniele (Renaissance and Reformation / Renaissance et Réforme, 2023)
This article aims to analyze the participation of the Italian poet Guittone d’Arezzo in the querelle des femmes, considering especially the poem Ahi lasso, che li boni e li malvagi, which anticipates some of the issues that would be central to the debate on female dignity in the following centuries. In his text, Guittone plays with paradox, overturning, undoing, and giving new form to the concepts of superiority and inferiority between men and women in order to exculpate the female sex. Later on, his arguments will serve not only some authors of the querelle but also writers such as Isotta Nogarola, Arcangela Tarabotti, and Moderata Fonte.